Measuring Satisfaction of Mutual Fund Investors from the Customer Communication Dimension of the Marketing Mix - Bhowal, Amalesh; Paul, Tarak (Indian Journal of Marketing, 2014)
The concept of 'customer satisfaction' is always seen as a widely accepted area of research amongst the academicians. Studies on customer satisfaction have showed that customer satisfaction is strongly dependent on the perceived experience and prior expectation of the customers. The gap between the level of expectations and the level of experience act as an indicator of the success or the future prospects of a product. A product is expected to satisfy the needs and expectations of the customers. Similarly, mutual funds are expected to fulfil the investment needs of the investors. This paper assessed the retail investors' level of experience and level of expectations from mutual fund investments in terms of the 'customer communication dimension' of the marketing mix. The study was conducted in Guwahati with a sample size of 405 respondents. The findings of the study showed that a large chunk of the investors were dissatisfied with mutual fund investments, and a significant gap was observed between the level of expectations and the level of experience (from the viewpoint of customer communication dimension of the marketing mix).